Spinal meningeal cyst in a child with Marfan syndrome: A potential cause for apparent dural puncture during caudal epidural block. Issue 9 (1st August 2019) - Ackermann, Irene; Henze, Georg; Kottke, Raimund; Weiss, Markus
Abstract: We report a complication from caudal epidural block for anesthesia in a 4‐year‐old child with Marfan syndrome who was undergoing lensectomy, orchidopexy, and circumcision resulting in apparent accidental dural puncture. Subsequent magnetic resonance imaging revealed a lumbosacral spinal meningeal cyst.